Diagnostic and predictive value of aEEG in newborns in critical state under sedation - A. A. Zadvornov; E. V. Grigoriev (Вестник анестезиологии и реаниматологии)
The objective: to study the diagnostic and prognostic value of amplitude-integrated electroencephalography (aEEG) in sedated neonates in critical state, through testing the level of S100B protein. Subjects and methods: 44 patients were enrolled in the study. The study group included patients with pathological patterns of 24-hour aEEG, in the control group, all patients had normal patterns. The level of serum S100B protein was compared in the groups on the 1st and 7th day of life as well as the early neurological outcome which was used to assess the prognostic significance of aEEG. In addition, the cut-off point of S100B in predicting an adverse outcome was estimated.Results. There were no significant difference in the level of S100B of the 1st day of life between the groups, however, there was a correlation between the severity of depression of electrocortical activity and the level of S100B protein (tau = -0.36, p < 0.001). On the 7th day of life, the level of S100B protein was significantly (p = 0.047) higher in the study group (337 (251; 819) ng/l) compared to the control group (259 (136; 354) ng/l). Elevation of S100B protein by the 7th day of life was not associated with pathological aEEG patterns or the outcome. aEEG sensitivity (Se) was 87%, specificity (Sp) ‒ 62%. The cut-off point for S100B of the first day of life was 493 ng/l with Se of 52% and Sp of 91%.Conclusion. There is a correlation between the severity of depression of electrocortical activity recorded by aEEG and S100B level on the 1st and 7th days of life,which confirms the diagnostic value of aEEG in newborns in critical state despite the use of sedation. The elevated level of S100B in the first week of life has neither diagnostic nor prognostic significance. aEEG has the highest predictive sensitivity, and S100B above 493 ng/l has the highest predictive specificity.